The Influence of Spiritual Motivation, Organizational Commitment, Job Satisfaction on Performance in the University of Batam - Ngaliman, Ngaliman (Opción, 2019)
This research aims to investigatethe influence of spiritual motivation, organ- izational commitment and job satisfaction on lecturers’ performance in the University of Batam. This study attempts to answer the question on a declin- ing trend of lecturers’ performance in the University of Batam in the last few years. All lecturers in the University Centre of 121 are population in this re- search. The study chose 93 people as the samples of this study. After the data werecollected, the data were analysed by using path analysis. The results of this study show that; first, the spiritual motivation directly and positively in- fluences job satisfaction. Second, organizational commitment positively affects job satisfaction.Third, the spiritual Motivation positively affects performance. Fourth, the organization does not have a direct positive influence on perfor- mance. Fifth, job satisfaction directly and positively influencesperformance.